Plasticity of the Cuticular Transpiration Barrier in Response to Water Shortage and Resupply in Camellia sinensis: A Role of Cuticular Waxes - Zhang, Yi; Du, Zhenghua; Han, Yanting; Chen, Xiaobing; Kong, Xiangrui; Sun, Weijiang; Chen, Changsong; Chen, Mingjie (Frontiers in Plant Science, 2021)
The cuticle is regarded as a non-living tissue; it remains unknown whether the cuticle could be reversibly modified and what are the potential mechanisms. In this study, three tea germplasms (Wuniuzao, 0202-10, and 0306A) were subjected to water deprivation followed by rehydration. The epicuticular waxes and intracuticular waxes from both leaf surfaces were quantified from the mature 5th leaf. Cuticular transpiration rates were then measured from leaf drying curves, and the correlations between cuticular transpiration rates and cuticular wax coverage were analyzed. We found that the cuticular transpiration barriers were reinforced by drought and reversed by rehydration treatment; the initial weak cuticular transpiration barriers were preferentially reinforced by drought stress, while the original major cuticular transpiration barriers were either strengthened or unaltered. Correlation analysis suggests that cuticle modifications could be realized by selective deposition of specific wax compounds into individual cuticular compartments through multiple mechanisms, including in vivo wax synthesis or transport, dynamic phase separation between epicuticular waxes and the intracuticular waxes, in vitro polymerization, and retro transportation into epidermal cell wall or protoplast for further transformation. Our data suggest that modifications of a limited set of specific wax components from individual cuticular compartments are sufficient to alter cuticular transpiration barrier properties.